MODEL PEMBELAJARAN PENJASORKES KID’S ATLETIK MELALUI PERMAINAN THE STRENGTH POST PADA SISWA SD KELAS V. (Department of Physical Education, Sport, Health and Recreation, 2013)
A model of learning penjasorkes kid athletic game ' s through the strength post is a method of learning basicjump, motion to run and throw by means of a game the strenght post on the kids class v sdn 03 gunungpati,sub-district gunungpati, the city of semarang 2012. The purpose of this research to produce a model of learningkid' s athletic and increase the power of lasting the body through the game of the strength post on the kids classv public elementary 03 gunungpati in learning penjasorkes so that it can develop a variety of aspects of learningand increasing the activity of corporeal students. A method of this research is research, development. Theprocedure product development covering analysis products to be developed, early, developing products expertsand revision, validation the trial of a group of small and revision, the trial of large groups and the final product.Collecting data was done using observations on the court and a questionnaire that obtained from the evaluationof the experts and the result The data collected from expert evaluation obtained the percentage of average resultanalysis product of 96 % with criteria very well. Hence can be used to trial smaii group. Data a questionnairestudents on trial clusters of small obtained average answer by the percentage 89,21 % with good category. Anddata a questionnaire students trial large groups obtained answer by the percentage 93,68 %. With category verywell. Students have not had a hard when playing the game strenght the post. Besides, after doing game strenghtthe post the pulse students increase. In learning penjasorkes needed learning variatif, innovative and not boring.For teachers penjasorkes in primary school expected to use the model game strenght the post this effectively